2020
DOI: 10.3389/fphys.2020.00983
|View full text |Cite
|
Sign up to set email alerts
|

Organ System Network Disruption Is Associated With Poor Prognosis in Patients With Chronic Liver Failure

Abstract: Background: A healthy individual has a high degree of functional connectivity between organ systems, which can be represented graphically in a network map. Disruption of this system connectivity is associated with mortality in life-threatening acute illnesses, demonstrated by a network approach. However, this approach has not been applied to chronic multisystem diseases and may be more reliable than conventional individual organ prognostic scoring methods. Cirrhosis is a chronic disease of the liver with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 83 publications
(97 reference statements)
1
13
0
Order By: Relevance
“…Their results showed that in a cohort of critically ill patients, survivors consistently exhibited a higher number of edges and clusters compared to non-survivors in their organ connectivity network structures (Asada et al, 2016). In a recent report, we used a similar approach and showed that functional connectivity of organ systems is significantly disrupted in patients with cirrhosis who did not survive during 12-month follow up (Tan et al, 2020). However, the methodology of these studies is based on correlation analysis of a population of patients and cannot be used for mapping the network connectivity at the level of individual patients.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their results showed that in a cohort of critically ill patients, survivors consistently exhibited a higher number of edges and clusters compared to non-survivors in their organ connectivity network structures (Asada et al, 2016). In a recent report, we used a similar approach and showed that functional connectivity of organ systems is significantly disrupted in patients with cirrhosis who did not survive during 12-month follow up (Tan et al, 2020). However, the methodology of these studies is based on correlation analysis of a population of patients and cannot be used for mapping the network connectivity at the level of individual patients.…”
Section: Introductionmentioning
confidence: 92%
“…Seven standard clinical variables representing unique physiological functions or clinical feature were collected (serum albumin, ALB; total bilirubin, Bil; prothrombin time, PT; serum creatinine, Cr; ammonia, NH 4 ; serum sodium, Na; and hepatic encephalopathy, HE) based on a previous study (Tan et al, 2020). HE was classified as unimpaired, minimal and overt HE according to Montagnese et al (Montagnese et al, 2004;Vilstrup et al, 2014).…”
Section: Clinical Laboratory Variablesmentioning
confidence: 99%
“…Alteration in the interactions within a layer will not only change the dynamics of that layer but also those of interacting layers, and thereby shift the integrated function of the system-as-a-whole ( 39 , 40 ). Physiological network properties have pragmatic clinical implications as exemplified in patients with liver failure ( 41 ) or severe critical illness ( 42 )—the breakdown/loss of network interconnection between the layers of system organization is associated with poor outcomes.…”
Section: Health Patterns—the Outcome Of Complex-adaptive Dynamicsmentioning
confidence: 99%
“…In recent years, the Network Physiology framework has been utilized in various fields of basic Physiology and Clinical Medicine, including multiple organ failure and sepsis in critically ill patients (Asada et al, 2016;Moorman et al, 2016), neonatal intensive care (Lavanga et al, 2020;Lucchini et al, 2020), liver disease (Tan et al, 2020), epilepsy and neurological disorders (Lin et al, 2020), diabetes and obesity (Podobnik et al, 2020;Prats-Puig et al, 2020), cancer (Liu et al, 2020), or psychiatry (Bolton et al, 2020), and has the potential for broad applications in the field of Exercise Physiology and Sports Medicine to uncover how the key physiological systems interact pairwise, that is, which links are the major mediators in a given network and how these links adjust their strength with accumulation of fatigue, after a training intervention, or in response to a certain pathological condition (e.g., musculoskeletal injury and neurodegenerative disease).…”
Section: Introductionmentioning
confidence: 99%